Electromagnetics explained a handbook for wireless/RF, EMC, and high-speed electronics - Schmitt, Ron. (Amsterdam ; Boston : Newnes, 2002)
Based on familiar circuit theory and basic physics, this book serves as an invaluable reference for both analog and digital engineers alike. For those who work with analog RF, this book is a must-have resource. With computers and networking equipment of the 21st century running at such high frequencies, it is now crucial for digital designers to understand electromagnetic fields, radiation and transmission lines. This knowledge is necessary for maintaining signal integrity and achieving EMC compliance. Since many digital designers are lacking in analog design skills, let alone electromagnetics, an easy-to-read but informative book on electromagnetic topics should be considered a welcome addition to their professional libraries. Covers topics using conceptual explanations and over 150 lucid figures, in place of complex mathematicsDemystifies antennas, waveguides, and transmission line phenomenaProvides the foundation necessary to thoroughly understand signal integrity issues associated with high-speed digital design.
Introduction and survey of the electromagnetic spectrum -- Fundamentals of electric fields -- Fundamentals of magnetic fields -- Electrodynamics -- Radiation -- Relativity and quantum physics -- Hidden schematic -- Transmission lines -- Waveguides and shields -- Circuits as guides for waves and S-parameters -- Antennas: how to make circuits that radiate -- EMC -- Lenses, dishes, and antenna arrays -- Diffraction -- Frequency dependence of materials, thermal radiation, and noise.
Includes bibliographical references and index.
Keywords: Electronics; Radio; Electromagnetic theory; Electronic books